Karakterisasi Alginat Dari Ganggang Coklat (Sargassum crassifolium Mont.) Hasil Proses Isolasi Menggunakan CaCl2 8% - Auzal Halim; Zilfia Zilfia; Maria Dona Octavia (Jurnal Farmasi Higea, 2010)
Sodium alginate was isolated from brown algae (Sargassum crassifoluim Mont) which  collected from Sungai Nipah Beach West Sumatera using Na2CO3 3% for 5 days at a temperature of 50C. Filtrate obtained then added with 8% CaCl2 solution with variation in leght of maceration for t is 3, 5 and 7 days. Sodium generated per each long imaceration  was 14:08%, 26.67% and 30.56%. The results showed that with increasing in macerating time, the yield obtained sodium alginate will also increase. Highest contain obtained from 7 days maceration. Sodium alginat obtained then  characterized that includes checking the purity, particle size determination, development index, examination IR spectra, viscosity and flow properties